Benefit‐finding experiences of cervical cancer survivors in rural Yunnan province, China: A qualitative study - Liyuan Sun; Ke Liu; Xilin Li; Yao Zhang; Zhilan Huang (Wiley, 2022)
Abstract Aim To explore and describe cervical cancer patients' benefit‐finding experiences in rural China. Design The phenomenological approach was used in this qualitative study. Methods In‐depth, semi‐structured interviews were conducted with 21 patients, from July to August of 2019. The data, which were collected, were analysed using the Colaizzi analysis procedure. Results According to the analysis results, the four benefit‐finding experience themes of the cervical cancer patients were, respectively, determined to be as follows: Health cognition and behaviour changes; reshaping of personal strength; focussing on relationships with others; and facing life positively. Conclusions The individual's cognition of health and their own strong qualities, and their external social support systems and information obtained and transmitted through interpersonal interactions, can promote the benefit finding. The findings suggest that medical staff should understand the traditional concepts of their patients, use their positive psychological potential, and build targeted nursing measures.